Bandwitdth efficient hybrid wireless-optical broadband-access network (WOBAN) based on OFDM transmission - Mohammad, Abu Bakar (2011)
In this paper, a simple and bandwidth efficient hybrid wireless-optical broadband access network (WOBAN) based on orthogonal frequency division multiplexing (OFDM) is proposed and designed. It is an optimal combination of an optical backhaul and a wireless front-end for an efficient access network. The bandwidth efficient WOBAN based on OFDM provides an effective solution to eliminate intersymbol interference (ISI) caused by dispersive channels. There are two factors considered important here; multipath fading in wireless link and dispersion effects in fiber link. The physical layer performance is analyzed in terms of bit error rate (BER), error vector magnitude (EVM), and signal-to-noise ratio (SNR). An 8 Gb/s data rate has been achieved by the optical backhaul along optical fiber length of 20 km. The wireless front-end access point supports data rate up to 240 Mb/s along an outdoor wireless link.